Binder and its preparation method and application
By using polyvinylidene fluoride with a weight average molecular weight of 1.5 million to 5 million as the binder, the problems of poor brittleness of the electrode sheet and reduced battery circulation performance caused by excessive adhesive use in traditional technology are solved, and the effect of reducing the binder usage is achieved, while maintaining or improving the bonding performance.
Patent Information
- Application Number
- CN202280002865.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-16
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-06-16
AI Technical Summary
The amount of polyvinylidene fluoride binder used in traditional lithium-ion batteries is too high, resulting in poor brittleness of the electrode sheet and degradation of battery circulation performance.
Polyvinylidene fluoride with a weight average molecular weight of 1.5 million to 5 million is used as the binder. By controlling its polydispersion coefficient, number average molecular weight, Dv50 particle size and crystallinity, the amount of binder is used, while maintaining or improving the bonding performance.
The content of binder in the active material layer is effectively reduced, the brittleness of the electrode sheet and the circulation performance of the battery are improved, and the adhesion force is not affected.
Smart Images

Figure CN115867625B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of secondary batteries, and more specifically to a binder and a preparation method and application thereof. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] Secondary batteries, such as lithium-ion batteries, often need to add binders to the positive electrode active material layer to enhance the bonding between the active material layer and the current collector, as well as the bonding between the active material particles. Polyvinylidene fluoride is one of the most widely used binder types in lithium-ion batteries. It has the advantages of strong bonding, insolubility in electrolyte, no reaction with electrolyte, not easy to crack after repeated charging, and no significant decrease in bonding. However, in traditional technology, the amount of polyvinylidene fluoride used as a binder often accounts for more than 2.5% of the mass of the raw materials of the active material layer. If the amount of binder is too high, it will squeeze the proportion of active materials in the active material layer, often resulting in brittle pole pieces, poor toughness, and reduced battery cycle performance. Summary of the invention
[0004] According to various embodiments of the present application, an adhesive and a preparation method and application thereof are provided.
[0005] In a first aspect of the present application, a binder is provided, comprising polyvinylidene fluoride having a weight average molecular weight of 1.5 to 5 million; optionally, the weight average molecular weight of the polyvinylidene fluoride is 1.8 to 3.2 million.
[0006] By selecting polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million as a binder component, when the binder is used in the preparation of lithium-ion battery pole pieces, the binder content in the active material layer can be effectively reduced, thereby overcoming the defects of the traditional technology such as brittle pole pieces and impaired battery cycle performance caused by excessive use of binders. At the same time, the bonding force between the components of the active material layer and between the active material layer and the current collector will not be reduced.
[0007] In some embodiments, the polydispersity coefficient of the polyvinylidene fluoride is 1.5 to 2.5; optionally, the polydispersity coefficient of the polyvinylidene fluoride is 2 to 2.3. A suitable polydispersity coefficient can make the polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million better dispersed in the solvent when preparing the positive electrode slurry, thereby effectively increasing the solid content of the slurry and reducing the production cost.
[0008] In some embodiments, the number average molecular weight of the polyvinylidene fluoride is 600,000 to 3,000,000; alternatively, the number average molecular weight of the polyvinylidene fluoride is 1,000,000 to 2,000,000. By controlling the number average molecular weight of the polyvinylidene fluoride within a certain range, the polydispersity coefficient of the polyvinylidene fluoride can be within a suitable range.
[0009] In some embodiments, the Dv50 particle size of the polyvinylidene fluoride is 50 μm to 150 μm; optionally, the Dv50 particle size of the polyvinylidene fluoride is 60 μm to 100 μm. Controlling the Dv50 particle size of polyvinylidene fluoride within a suitable range can make polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million have a suitable solubility. When used to prepare positive electrode plates of lithium-ion batteries, it can not only increase the dissolution rate of high molecular weight polyvinylidene fluoride, thereby speeding up the preparation of positive electrode slurry, but most importantly, it can also control the amount of binder to a lower level without causing excessive negative impact on the bonding performance, thereby effectively improving the damage to the performance of the plate and battery caused by high amount of binder in traditional technology.
[0010] In some embodiments, the crystallinity of the polyvinylidene fluoride is 38% to 52%; alternatively, the crystallinity of the polyvinylidene fluoride is 38% to 48%; more alternatively, the crystallinity of the polyvinylidene fluoride is 40% to 45%. The crystallinity of polyvinylidene fluoride also affects its solubility, so the appropriate crystallinity range is also an important factor in maintaining the amount of binder at a low level.
[0011] In some embodiments, the viscosity of the binder solution prepared by dissolving the polyvinylidene fluoride in N-methylpyrrolidone is 2500 mPa·s~6500 mPa·s; it can be 3500 mPa·s~6500 mPa·s, and more preferably 3500mPa·s~5000mPa·s, and in the binder solution, the mass percentage of the binder is 3%~5%. When preparing the positive electrode slurry, the binder solution needs to have a certain viscosity to prevent the sedimentation of the positive electrode active material and auxiliary agents such as the conductive agent, so that the slurry can be placed more stably. In traditional technology, to achieve a solution viscosity of 3500mPa·s~5000mPa·s, at least 7% mass percentage of the binder is required to achieve it. By using the binder of the present application, the amount of the binder can be controlled within the range of 3%~5%, which provides the possibility for the subsequent binder to have a lower content in the positive electrode active material layer.
[0012] In a second aspect of the present application, a method for preparing the binder according to one or more of the above embodiments is provided, comprising the following steps:
[0013] The vinylidene fluoride monomer is polymerized for 6h~12h in a non-reactive gas atmosphere, a reaction pressure of 6MPa~9MPa, and a reaction temperature of 45°C~65°C; optionally, the reaction pressure is 6MPa~8Mpa; optionally, the reaction temperature is 45°C~60°C; optionally, the polymerization reaction time is 6h~10h;
[0014] Add chain transfer agent, wait until the pressure in the reaction system drops to 2MPa~2.5MPa, stop the reaction, separate the solid and liquid, and retain the solid phase.
[0015] By controlling the temperature, pressure and time of the polymerization reaction within an appropriate range, vinylidene fluoride can react in the form of homopolymerization, thereby obtaining polyvinylidene fluoride with higher regularity, and the weight average molecular weight of polyvinylidene fluoride can be controlled within a preset range to achieve a low dosage of binder in the positive electrode slurry.
[0016] In some embodiments, the chain transfer agent includes one or more of cyclohexane, isopropanol, methanol, and acetone.
[0017] In some embodiments, the amount of the chain transfer agent is 1.5% to 3% of the mass of the vinylidene fluoride monomer. The amount of the chain transfer agent is controlled within a suitable range, so that the polymer chain length can be controlled, thereby obtaining a polyvinylidene fluoride product with a suitable molecular weight range.
[0018] In some embodiments, the polymerization reaction comprises the following steps:
[0019] Adding a solvent and a dispersant into a container, evacuating the container and then filling it with a non-reactive gas;
[0020] Adding an initiator and a pH adjuster into the container, adjusting the pH value to 6.5-7, and then adding vinylidene fluoride monomer to make the pressure in the container reach the reaction pressure;
[0021] After stirring for 30 min to 60 min, the temperature is raised to the reaction temperature to carry out a polymerization reaction.
[0022] Before heating up for polymerization reaction, the materials are first mixed evenly, so that the reaction can proceed more thoroughly and the polydispersity coefficient, crystallinity and particle size of the obtained polyvinylidene fluoride are more appropriate.
[0023] In some embodiments, the amount of the solvent used is 2 to 8 times the mass of the vinylidene fluoride monomer.
[0024] In some embodiments, the dispersant includes one or more of cellulose ether and polyvinyl alcohol; alternatively, the cellulose ether includes one or more of methyl cellulose ether and carboxyethyl cellulose ether.
[0025] In some embodiments, the amount of the dispersant is 0.1% to 0.3% of the mass of the vinylidene fluoride monomer.
[0026] In some embodiments, the initiator is an organic peroxide; optionally, the organic peroxide includes one or more of tert-amyl peroxypivalate, tert-amyl peroxypivalate, 2-ethyl peroxydicarbonate, diisopropyl peroxydicarbonate and tert-butyl peroxypivalate.
[0027] In some embodiments, the amount of the initiator used is 0.15% to 1% of the mass of the vinylidene fluoride monomer.
[0028] In some embodiments, the pH adjuster includes one or more of potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate and ammonia water.
[0029] In some embodiments, the pH adjuster is used in an amount of 0.05% to 0.2% by mass of the vinylidene fluoride monomer.
[0030] The third aspect of the present application provides the use of polyvinylidene fluoride defined in one or more of the aforementioned embodiments in the preparation of a binder.
[0031] In a fourth aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet;
[0032] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the binder described in one or more of the above embodiments.
[0033] In some embodiments, in the positive electrode active material layer, the mass percentage of the binder is 0.6% to 1.8%, optionally 0.6% to 1.2%; optionally, the mass percentage of the binder is 0.6% to 0.8%. In conventional technology, the amount of binder in the positive electrode active material layer is often as high as 2.5% or more. When the amount drops to 2% or less, it will significantly affect the bonding between the particles of the positive electrode active material layer, or the bonding between the active material layer and the current collector. The use of the binder in this application can greatly reduce the amount of binder to 1.2% or less compared to conventional technology, and does not significantly affect the bonding performance. The low amount of binder effectively improves the brittleness and cycle performance of the pole piece.
[0034] In a fifth aspect of the present application, a battery module is provided, comprising the secondary battery described in one or more of the aforementioned embodiments.
[0035] In a sixth aspect of the present application, a battery pack is provided, comprising the aforementioned battery module.
[0036] In a seventh aspect of the present application, there is provided an electrical device comprising one or more of the secondary batteries described in one or more of the aforementioned embodiments, the aforementioned battery modules, and the aforementioned battery packs.
[0037] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to better describe and illustrate the embodiments or examples of those applications disclosed herein, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the embodiments or examples currently described, and the best modes of these applications currently understood.
[0039] Figure 1 This is a scanning electron microscope image of polyvinylidene fluoride particles according to one embodiment of the present application.
[0040] Figure 2 This is a scanning electron microscope image of polyvinylidene fluoride particles according to one embodiment of the present application.
[0041] Figure 3 This is a scanning electron microscope image of polyvinylidene fluoride particles according to one embodiment of the present application.
[0042] Figure 4 This is a scanning electron microscope image of polyvinylidene fluoride particles according to one embodiment of the present application.
[0043] Figure 5 This is a scanning electron microscope image of comparative example 1 of the present application.
[0044] Figure 6 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0045] Figure 7 yes Figure 6 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0046] Figure 8 is a schematic diagram of a battery module according to an embodiment of the present application.
[0047] Fig. 9 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0048] Fig.10 yes Fig. 9 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0049] Fig.11 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0050] Description of reference numerals:
[0051] 1: battery pack; 2: upper box; 3: lower box; 4: battery module; 5: secondary battery; 51: shell; 52: electrode assembly; 53: cover plate. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0054] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0055] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0056] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0057] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0058] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0059] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0060] In general, the binder is an indispensable raw material for preparing the positive electrode active material layer. It provides bonding force between the raw material particles of the active material layer, and between the active material layer and the current collector layer, ensuring that the secondary battery can operate normally during multiple charge and discharge processes. In order to ensure sufficient bonding force, in traditional technology, it is generally necessary to use a binder with a mass percentage of more than 2.5% of the positive electrode active material layer. However, too high a binder dosage will cause the finished electrode sheet to be brittle, easy to crack during use and processing, affecting the production yield and safety of the battery. Moreover, too high a binder content is not conducive to the cycle performance of the battery. Therefore, how to reduce the amount of binder in the positive electrode active material layer without negatively affecting its bonding performance is an urgent problem to be solved in the field of secondary batteries.
[0061] Based on this, an embodiment of the present application provides a binder, which includes polyvinylidene fluoride having a weight average molecular weight of 1.5 to 5 million; optionally, the weight average molecular weight of the polyvinylidene fluoride is 1.8 to 3.2 million. The weight average molecular weight of polyvinylidene fluoride can also be, for example, 1.5 million, 1.6 million, 1.7 million, 1.8 million, 1.9 million, 2 million, 2.1 million, 2.2 million, 2.3 million, 2.4 million, 2.5 million, 2.6 million, 2.7 million, 2.8 million, 2.9 million, 3 million, 3.1 million, 3.2 million, 3.3 million, 3.4 million, 3.5 million, 3.6 million, 3.7 million, 3.8 million, 3.9 million, 4 million, 4.1 million, 4.2 million, 4.3 million, 4.4 million, 4.5 million, 4.6 million, 4.7 million, 4.8 million, 4.9 million or 5 million, or within the range of any two of the above points.
[0062] By selecting polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million as a binder component, when the binder is used in the preparation of lithium-ion battery pole pieces, the binder content in the active material layer can be effectively reduced, thereby overcoming the defects of the traditional technology such as brittle pole pieces and impaired battery cycle performance caused by excessive use of binders. At the same time, the bonding force between the components of the active material layer and between the active material layer and the current collector will not be reduced.
[0063] In some embodiments, the polydispersity coefficient of polyvinylidene fluoride is 1.5 to 2.5; alternatively, the polydispersity coefficient of polyvinylidene fluoride is 2 to 2.4, 2 to 2.3 or 2.1 to 2.4. The polydispersity coefficient of polyvinylidene fluoride can also be, for example, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, or within the range of any two of the above point values. A suitable polydispersity coefficient can make the polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million better dispersed in the solvent when preparing the positive electrode slurry, thereby effectively increasing the solid content of the slurry and reducing the production cost.
[0064] In this application, the polydispersity coefficient can be tested by methods known in the art, for example, using a Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141). A polystyrene solution sample with a mass fraction of 3.0% is used as a reference, and a matching chromatographic column (oily: Styragel HT5 DMF7.8*300mm+Styragel HT4) is selected. A 3.0% binder glue solution is prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution is allowed to stand for one day for standby use. During the test, tetrahydrofuran is first drawn with a syringe, rinsed, and repeated several times. Then 5 ml of the experimental solution is drawn, the air in the syringe is removed, and the needle tip is wiped dry. Finally, the sample solution is slowly injected into the injection port. The data is obtained after the indication is stable. The weight average molecular weight a and the number average molecular weight b are read respectively. Polydispersity coefficient = a / b.
[0065] In some embodiments, the number average molecular weight of polyvinylidene fluoride is 600,000 to 3 million; alternatively, the number average molecular weight of polyvinylidene fluoride is 1 million to 2 million. The number average molecular weight of polyvinylidene fluoride can also be, for example, 600,000, 700,000, 800,000, 900,000, 1 million, 1.1 million, 1.2 million, 1.3 million, 1.4 million, 1.5 million, 1.6 million, 1.7 million, 1.8 million, 1.9 million, 2 million, 2.5 million or 3 million, or within the range of any two of the above point values. By controlling the number average molecular weight of polyvinylidene fluoride within a certain range, the polydispersity coefficient of polyvinylidene fluoride can be within a suitable range.
[0066] In some embodiments, the Dv50 particle size of the polyvinylidene fluoride is 50 μm to 150 μm; optionally, the Dv50 particle size of the polyvinylidene fluoride is 60 μm to 100 μm. The Dv50 particle size of the polyvinylidene fluoride can also be, for example, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, or within the range of any two of the above point values. Controlling the Dv50 particle size of polyvinylidene fluoride within an appropriate range can make polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million have an appropriate solubility. When used in the preparation of positive electrode plates of lithium-ion batteries, it can not only increase the dissolution rate of large molecular weight polyvinylidene fluoride, thereby accelerating the preparation of positive electrode slurry, but most importantly, it can also control the amount of binder at a lower level without causing excessive negative impact on the bonding performance, thereby effectively improving the damage to the plate and battery performance caused by high dosage of binder in traditional technologies.
[0067] In this application, Dv50 refers to: in the particle size distribution curve, the particle size corresponding to the cumulative particle size distribution number of the particles reaches 50%, and its physical meaning is that the particles with a particle size smaller (or larger) than it account for 50%. As an example, Dv50 can be conveniently measured by a laser particle size analyzer with reference to GB / T19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.
[0068] like Figure 1~Figure 4 , shows a scanning electron microscope image of polyvinylidene fluoride particles of some embodiments. Figure 5 The scanning electron microscope image of the polyvinylidene fluoride particles of Comparative Example 1 is shown.
[0069] In some embodiments, the crystallinity of polyvinylidene fluoride is 38% to 52%; alternatively, the crystallinity of polyvinylidene fluoride is 38% to 48%; alternatively, the crystallinity of polyvinylidene fluoride is 40% to 45%. The crystallinity of polyvinylidene fluoride can also be, for example, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 48%, 52%, or within the range of any two of the above point values. The crystallinity of polyvinylidene fluoride also affects its solubility, so the appropriate crystallinity range is also an important factor in maintaining the amount of binder at a low level.
[0070] In the present application, the crystallinity test can be carried out by methods known in the art, for example, the crystallinity can be measured by differential scanning calorimetry (DSC). DSC can measure the heat released when a crystalline polymer melts. This heat is the melting heat ΔHf of the crystalline portion of the polymer. The melting heat of the polymer is proportional to its crystallinity. Therefore, the crystallinity θ = partial crystallization melting heat of the polymer / 100% crystallization melting heat of the polymer × 100%, wherein the 100% crystallization melting heat of the polymer is known.
[0071] In some embodiments, the viscosity of the binder solution prepared by dissolving polyvinylidene fluoride in N-methylpyrrolidone is 2500 mPa·s to 6500 mPa·s, and can be 3500 mPa·s to 6500 mPa·s, and can be 3500 mPa·s to 5000 mPa·s, and the mass percentage of the binder in the binder solution is 3% to 5%. The viscosity of the binder solution can also be, for example, 2500 mPa·s, 3000 mPa·s, 3500 mPa·s, 3750 mPa·s, 4000 mPa·s, 4250 mPa·s, 4500 mPa·s, 4750 mPa·s, 4900 mPa·s, 5000 mPa·s, 6500 mPa·s, or within the range of any two of the above point values. When preparing positive electrode slurry, the binder solution needs to have a certain viscosity to prevent the sedimentation of positive electrode active materials and additives such as conductive agents, so that the slurry can be placed more stably. In traditional technology, to achieve a solution viscosity of 3500mPa·s~5000mPa·s, at least 7% by mass of binder is required to achieve it. By using the binder of this application, the amount of binder can be controlled within the range of 3%~5%, which provides the possibility for the subsequent binder to have a lower content in the positive electrode active material layer.
[0072] Furthermore, when the mass percentage concentration of the polyvinylidene fluoride binder solution is 4 wt %, the viscosity thereof is 2500 mPa·s to 6500 mPa·s, and can be 3500 mPa·s to 6500 Pa, and can be 3500 mPa·s to 5000 mPa·s.
[0073] Furthermore, the solvent of the polyvinylidene fluoride binder solution is N-methylpyrrolidone.
[0074] In the present application, the viscosity of the binder solution can be tested by methods known in the art. As an example, the viscosity of the binder solution can be tested by using an Anton Paar rotational rheometer to test the dynamic viscosity of the material at a shear rate of 0.1 s -1 ~100 s -1 , 31 points are measured and the consistency coefficient is obtained after fitting, which can characterize the viscosity of the binder solution.
[0075] In a second aspect of the present application, a method for preparing the binder of one or more of the above embodiments is provided, comprising the following steps:
[0076] The vinylidene fluoride monomer is polymerized in a non-reactive gas atmosphere, a reaction pressure of 6MPa~9MPa, and a reaction temperature of 45℃~65℃ for 6h~12h; optionally, the reaction pressure is 6MPa~8Mpa; optionally, the reaction temperature is 45℃~60℃; optionally, the polymerization reaction time is 6h~10h.
[0077] Add chain transfer agent, wait until the pressure in the reaction system drops to 2MPa~2.5MPa, stop the reaction, separate the solid and liquid, and retain the solid phase.
[0078] It can be understood that the non-reactive gas refers to a gas that does not react with the reactants in the reaction system. Common non-reactive gases may include, for example, inert gases such as argon and nitrogen.
[0079] In some embodiments, the reaction pressure may be, for example, 6.5 MPa, 7 MPa, 7.5 MPa, 8 MPa, or 9 MPa.
[0080] In some embodiments, the reaction temperature may be, for example, 45°C, 50°C, 55°C, 60°C, or 65°C.
[0081] In some embodiments, the polymerization reaction time may be, for example, 6 h, 7 h, 8 h, 9 h, 10 h, or 12 h.
[0082] By controlling the temperature, pressure and time of the polymerization reaction within an appropriate range, vinylidene fluoride can react in the form of homopolymerization, thereby obtaining polyvinylidene fluoride with higher regularity, and the weight average molecular weight of polyvinylidene fluoride can be controlled within a preset range to achieve a low dosage of binder in the positive electrode slurry.
[0083] In some embodiments, the chain transfer agent includes one or more of cyclohexane, isopropanol, methanol, and acetone.
[0084] In some embodiments, the amount of the chain transfer agent is 1.5% to 3% of the mass of the vinylidene fluoride monomer, and the amount of the chain transfer agent can also be, for example, 2% or 2.5%. When the amount of the chain transfer agent is controlled within a suitable range, the polymer chain length can be controlled, thereby obtaining a polyvinylidene fluoride product with a suitable molecular weight range.
[0085] In some embodiments, the polymerization reaction comprises the following steps:
[0086] Adding a solvent and a dispersant into a container, evacuating the container and then filling it with a non-reactive gas;
[0087] Add an initiator and a pH adjuster into the container, adjust the pH value to 6.5-7, and then add vinylidene fluoride monomer to make the pressure in the container reach the above reaction pressure;
[0088] After stirring for 30 min to 60 min, the temperature is raised to the above reaction temperature to carry out the polymerization reaction.
[0089] Before heating up for polymerization reaction, the materials are first mixed evenly, so that the reaction can proceed more thoroughly and the polydispersity coefficient, crystallinity and particle size of the obtained polyvinylidene fluoride are more appropriate.
[0090] In some embodiments, the amount of the solvent is 2 to 8 times the mass of the vinylidene fluoride monomer. The amount of the solvent may also be, for example, 3, 4, 5, 6 or 7 times the mass of the vinylidene fluoride monomer. Suitable solvents may include, for example, water, preferably deionized water.
[0091] In some embodiments, the dispersant includes one or more of cellulose ether and polyvinyl alcohol; alternatively, the cellulose ether includes one or more of methyl cellulose ether and carboxyethyl cellulose ether.
[0092] In some embodiments, the amount of the dispersant is 0.1% to 0.3% of the mass of the vinylidene fluoride monomer. The amount of the dispersant may also be 0.2%, for example.
[0093] In some embodiments, the initiator is an organic peroxide; optionally, the organic peroxide includes one or more of tert-amyl peroxypivalate, tert-amyl peroxypivalate, 2-ethyl peroxydicarbonate, diisopropyl peroxydicarbonate, and tert-butyl peroxypivalate.
[0094] In some embodiments, the amount of the initiator is 0.15% to 1% of the mass of the vinylidene fluoride monomer. The amount of the initiator may also be, for example, 0.2%, 0.4%, 0.6% or 0.8%.
[0095] In some embodiments, the pH adjuster includes one or more of potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, and aqueous ammonia.
[0096] In some embodiments, the amount of the pH adjuster is 0.05% to 0.2% of the mass of the vinylidene fluoride monomer. The amount of the pH adjuster can also be, for example, 0.1% or 0.15%.
[0097] The third aspect of the present application provides the use of polyvinylidene fluoride defined in one or more of the aforementioned embodiments in the preparation of a binder.
[0098] In a fourth aspect of the present application, a secondary battery is provided, comprising a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet;
[0099] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a binder according to one or more of the aforementioned embodiments.
[0100] In some embodiments, in the positive electrode active material layer, the mass percentage of the binder is 0.6% to 1.8%, and optionally 0.6% to 1.2%; optionally, the mass percentage of the binder is 0.6% to 0.8%. The amount of binder used can also be, for example, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.8%. In traditional technology, the amount of binder used in the positive electrode active material layer is often as high as 2.5% or more. When the amount drops to 2% or less, it will significantly affect the adhesion between the particles of the positive electrode active material layer, or the adhesion between the active material layer and the current collector. The use of the binder in this application can greatly reduce the amount of binder used to 1.2% or less compared to traditional technology, and does not significantly affect the bonding performance. The low amount of binder effectively improves the brittleness and cycle performance of the pole piece.
[0101] In a fifth aspect of the present application, a battery module is provided, comprising a secondary battery according to one or more of the aforementioned embodiments.
[0102] In a sixth aspect of the present application, a battery pack is provided, comprising the aforementioned battery module.
[0103] In a seventh aspect of the present application, there is provided an electrical device comprising one or more of the secondary batteries of one or more of the aforementioned embodiments, the aforementioned battery modules, and the aforementioned battery packs.
[0104] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.
[0105] In one embodiment of the present application, a secondary battery is provided.
[0106] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0107] Positive electrode
[0108] The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode active material layer contains the binder provided in the first aspect of the present application.
[0109] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.
[0110] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0111] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0112] In some embodiments, the positive electrode active material layer may also optionally include other conventional binders in addition to the binder provided in the first aspect of the present application. As an example, the conventional binder may include at least one of polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0113] In some embodiments, the positive electrode active material layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0114] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0115] Negative electrode
[0116] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0117] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0118] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0119] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0120] In some embodiments, the negative electrode film layer may further include a binder, which may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0121] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0122] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0123] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0124] Electrolytes
[0125] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0126] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0127] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0128] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0129] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0130] Isolation film
[0131] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0132] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0133] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0134] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0135] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0136] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 6 The secondary battery 5 is a square structure as an example.
[0137] In some embodiments, reference Figure 7 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0138] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0139] Figure 8 4 is an example of a battery module. Figure 8 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0140] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0141] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0142] Fig. 9 and Fig.10 1 is a battery pack 1 as an example. Fig. 9 and Fig.10 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0143] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0144] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0145] Fig.11 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0146] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0147] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims.
[0148] The present application is further described in detail below in conjunction with specific examples and comparative examples. Experimental parameters not specified in the following specific examples are preferably referred to the instructions given in the present application documents, and may also refer to the experimental manual of the art or other experimental methods known in the art, or refer to the experimental conditions recommended by the manufacturer. It is understandable that the instruments and raw materials used in the following examples are more specific, and in other specific embodiments, they may not be limited thereto; the weight of the relevant components mentioned in the embodiments of the present application specification may not only refer to the specific content of each component, but may also represent the proportional relationship of the weight between each component, therefore, as long as the content of the relevant components of the present application specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present application specification. Specifically, the weight described in the present application specification may be μg, mg, g, kg and other mass units known in the chemical and chemical fields. The reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be obtained through commercial purchase. Example
[0149] (1) Preparation of polyvinylidene fluoride binder:
[0150] 4 kg of deionized water and 2 g of methyl cellulose ether were added to a 10 L autoclave, and the autoclave was evacuated and O2 was replaced with N2 three times. 5 g of tert-butyl peroxypivalate and 2 g of sodium bicarbonate were added again to adjust the pH value to 6.5-7, and 1 kg of vinylidene fluoride monomer was charged to make the pressure reach 7 MPa, and the mixture was mixed and stirred for 30 min, and the temperature was raised to 45° C. to carry out polymerization reaction; after 6 h of polymerization reaction, 30 g of cyclohexane was added to continue the reaction, and the reaction was stopped when the pressure in the autoclave dropped to 2 MPa; the reaction system was centrifuged and the solid phase was collected, and the polyvinylidene fluoride binder was obtained by washing and drying;
[0151] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 1.8 million, polydispersity coefficient 2.1, crystallinity 42%, Dv50 particle size 60 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 3600mPa·s; the scanning electron microscope image of the polyvinylidene fluoride particles prepared in this embodiment is as follows Figure 1 shown.
[0152] (2) Preparation of positive electrode slurry:
[0153] 3.99 kg of lithium iron phosphate, 32.8 g of the polyvinylidene fluoride binder prepared in step (1), 57.4 g of acetylene black, 12.3 g of a dispersant, and 2.4 kg of N-methylpyrrolidone (NMP) are uniformly mixed to obtain a positive electrode slurry; the mass percentage of the polyvinylidene fluoride binder in the solute of the positive electrode slurry is 0.8%;
[0154] (3) The positive electrode slurry prepared in step (2) is scraped onto the carbon-coated aluminum foil, baked at 110°C for 15 min, cold pressed and cut into discs with a diameter of 15 mm, and then made into a button cell with a metal lithium sheet, an isolation membrane, and an electrolyte.
[0155] Embodiment 2~5
[0156] The method is basically the same as Example 1, except that the mass percentages of the polyvinylidene fluoride binder in step (2) are 0.9%, 1%, 1.1% and 1.2% respectively. Example
[0157] The method is basically the same as Example 1, except that in step (1), after the polymerization reaction is carried out for 8 hours, 25 g of cyclohexane is added to continue the reaction;
[0158] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 2.5 million, polydispersity coefficient 2.1, crystallinity 44%, Dv50 particle size 80μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 4300mPa·s. The scanning electron microscope image of the polyvinylidene fluoride particles prepared in this embodiment is as follows: Figure 2 shown.
[0159] Embodiments 7 to 10
[0160] The method is basically the same as Example 6, except that the mass percentages of the polyvinylidene fluoride binder in step (2) are 0.9%, 1%, 1.1%, and 1.2%, respectively. Example
[0161] The process is basically the same as Example 1, except that, in step (1), after the polymerization reaction is carried out for 10 hours, 20 g of cyclohexane is added to continue the reaction;
[0162] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 3.2 million, polydispersity coefficient 2.2, crystallinity 45%, Dv50 particle size 100 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 4900mPa·s. The scanning electron microscope image of the polyvinylidene fluoride particles prepared in this embodiment is as follows: Figure 3 shown.
[0163] Embodiment 12-15
[0164] Basically the same as Example 11, except that the mass percentages of the polyvinylidene fluoride binder in step (2) are 0.9%, 1%, 1.1%, and 1.2%, respectively. Example
[0165] The method is basically the same as Example 1, except that in step (1), after the polymerization reaction is carried out for 12 hours, 15 g of cyclohexane is added to continue the reaction;
[0166] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 5 million, polydispersity coefficient 2.2, crystallinity 46%, Dv50 particle size 150μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 6500mPa·s. The scanning electron microscope image of the polyvinylidene fluoride particles prepared in this embodiment is as follows: Figure 4 shown.
[0167] Embodiment 17-18
[0168] It is basically the same as Example 16, except that the mass percentages of the polyvinylidene fluoride binder in step (2) are 0.6% and 0.7% respectively. Example
[0169] The process is basically the same as Example 1, except that, in step (1), after the polymerization reaction is carried out for 5 hours, 33 g of cyclohexane is added to continue the reaction;
[0170] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 1.5 million, polydispersity coefficient 2.18, crystallinity 41.5%, Dv50 particle size 45 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 3000mPa·s. Example
[0171] Basically the same as Example 19, except that the mass percentage of the polyvinylidene fluoride binder in step (2) is 1.8%. Example
[0172] The method is substantially the same as Example 1, except that the polymerization temperature in step (1) is 65°C;
[0173] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 2 million, polydispersity coefficient 2.4, crystallinity 52%, Dv50 particle size 50 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 4000mPa·s. Example
[0174] The method is basically the same as Example 1, except that the polymerization reaction time in step (1) is 12 h;
[0175] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 1.83 million, polydispersity coefficient 2.1, crystallinity 42%, Dv50 particle size 60 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 3700mPa·s. Example
[0176] The method is basically the same as Example 1, except that the polymerization reaction pressure in step (1) is 9 MPa;
[0177] The relevant parameters of the polyvinylidene fluoride binder prepared in this embodiment are as follows: weight average molecular weight 1.6 million, polydispersity coefficient 2.15, crystallinity 42%, Dv50 particle size 50 μm; the polyvinylidene fluoride binder prepared in this embodiment is dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity is measured to be 2500mPa·s.
[0178] Comparative Example 1
[0179] The method is basically the same as Example 1, except that in step (2), the polyvinylidene fluoride binder prepared in step (1) is replaced with commercially available polyvinylidene fluoride with a weight average molecular weight of 800,000 (701A brand produced by East Sunshine Company), so that the mass percentage of polyvinylidene fluoride in the slurry solute is 2.5%. The scanning electron microscope image of the polyvinylidene fluoride particles prepared in this comparative example is as follows: Figure 5 shown.
[0180] Comparative Example
[0181] The method is substantially the same as Example 1, except that the polymerization temperature in step (1) is 35°C;
[0182] The relevant parameters of the polyvinylidene fluoride binder prepared in this comparative example are as follows: weight average molecular weight 1.2 million, polydispersity coefficient 1.8, crystallinity 40%, Dv50 particle size 30 μm; the polyvinylidene fluoride binder prepared in this comparative example was dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity was measured to be 450mPa·s.
[0183] Comparative Example 3
[0184] The method is basically the same as Example 1, except that the polymerization reaction time in step (1) is 4 h;
[0185] The relevant parameters of the polyvinylidene fluoride binder prepared in this comparative example are as follows: weight average molecular weight 1.1 million, polydispersity coefficient 1.9, crystallinity 38%, Dv50 particle size 25 μm; the polyvinylidene fluoride binder prepared in this comparative example was dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity was measured to be 232mPa·s.
[0186] Comparative Example 4
[0187] The method is basically the same as Example 1, except that the polymerization reaction pressure in step (1) is 5 MPa;
[0188] The relevant parameters of the polyvinylidene fluoride binder prepared in this comparative example are as follows: weight average molecular weight 1.4 million, polydispersity coefficient 2.2, crystallinity 41%, Dv50 particle size 40 μm; the polyvinylidene fluoride binder prepared in this comparative example was dissolved in N-methylpyrrolidone solution to prepare a solution with a mass percentage concentration of 4wt%, and the solution viscosity was measured to be 1800mPa·s.
[0189] Characterization Tests:
[0190] The polyvinylidene fluoride binder, pole piece or button cell prepared in each embodiment and comparative example was subjected to the following characterization tests:
[0191] (1) Scanning the polyvinylidene fluoride binder by scanning electron microscopy to determine the morphology and particle size;
[0192] (2) Conduct a brittleness test on the electrode. The test steps are as follows:
[0193] The cold pressed electrode is sampled in the transverse direction, which can be (4cm×25cm longitudinally) 100cm 2 Sample area: 3 pieces, 100cm 2 (Fold in half according to 25cm longitudinal direction) Pre-fold, place the pre-folded experimental film on the experimental table plane, roll it once with a 2kg cylindrical roller, and check whether there are light leakage points under the light. If there are light leakage points, the sample does not meet the requirements. If there are no light leakage points, record the number of rolling times, and fold the experimental sample along the longitudinal crease, observe the crease against the light until a light transmission point appears and record the number of rolling times n1. Repeat the above operation to obtain the second and third light transmission rolling times n2 and n3, and calculate the average rolling times = (n1+n2+n3) / 3;
[0194] (3) Adhesion test: the test steps are as follows:
[0195] Refer to the national standard "Adhesive 180° Peel Strength Test Method", use a blade to cut a sample with a width of 30mm and a length of 100-160mm, and stick the special double-sided tape on the steel plate, with a tape width of 20mm and a length of 90-150mm. Stick the electrode sample cut earlier on the double-sided tape, with the test surface facing down, and then roll it three times in the same direction with a roller;
[0196] Insert a paper tape with the same width as the electrode and 80-200mm longer than the length of the sample under the electrode and fix it with wrinkle glue;
[0197] Turn on the power of the Sansi tensile testing machine (sensitivity is 1N), the indicator light is on, adjust the limit block to the appropriate position, and fix the end of the steel plate without the electrode with the lower clamp. Fold the paper tape upwards and fix it with the upper clamp, use the "up" and "down" buttons on the manual controller attached to the tensile testing machine to adjust the position of the upper clamp, then perform the test and read the value.
[0198] (4) Battery capacity retention rate test, the test steps are as follows:
[0199] The battery is charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 5 minutes, and then discharged to 2.5V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. The battery capacity retention rate after each cycle is Pn=Cn / C0*100%. The 100 point values of P1, P2...P100 are used as the vertical coordinates, and the corresponding number of cycles is used as the horizontal coordinates to obtain a curve graph of the battery capacity retention rate and the number of cycles;
[0200] During the test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 100th cycle corresponds to n=100; the battery capacity retention rate data is the data measured after 500 cycles under the above test conditions, that is, the value of P500.
[0201] The above test data are listed in Table 1:
[0202] Table 1
[0203]
[0204] Analyzing the data in Table 1 and comparing Example 1, Example 6, Example 11, Example 16, and Example 19, it can be seen that as the weight-average molecular weight increases, the Dv50 particle size, bonding force, and cycle performance of the binder generally show an upward trend, and the average number of rolling times of the pole piece will gradually decrease. As can be seen from Example 17, when the weight-average molecular weight of polyvinylidene fluoride reaches 5 million, only 0.6% of the dosage can provide a bonding force of 30.7 N / m, and the battery cycle performance is good, but the pole piece is slightly more brittle, but it is still better than the commercially available binder (Comparative Example 1). It can be seen that the binder provided in this application can effectively reduce the amount of binder used in the positive electrode active material, and provide good pole piece toughness, bonding force, and battery cycle performance.
[0205] Comparing Example 1 and Example 21, although the molecular weights of the two are close, the reaction temperature of Example 21 is relatively high, and the crystallinity and polydispersity coefficient of polyvinylidene fluoride prepared by the polymerization reaction are also relatively high, which affects the brittleness of the electrode and significantly reduces the average number of rolling times. Therefore, the polymerization reaction temperature is preferably controlled at 45°C~60°C, so that the crystallinity can be controlled in the appropriate range of 38%~48%, and the polydispersity coefficient can be controlled in the more preferred range of 2~2.3.
[0206] Comparing Examples 1 to 5, 6 to 10, 11 to 15, 16 to 18, and 19 to 20, it can be seen that as the amount of polyvinylidene fluoride increases, the adhesion and cycle performance increase, but the pole piece will gradually become brittle, and the average number of rolling times decreases. In particular, in Example 20, after the amount of binder is greatly increased to 1.8%, the improvement in cycle performance and adhesion becomes limited, but the number of rolling times will be significantly reduced.
[0207] Compared with Example 1, in Example 22, the polymerization reaction time is longer. With the continuous consumption of the monomer and the decrease in pressure, the polymerization conditions are no longer met. Prolonging the reaction time cannot continue the polymerization reaction. Therefore, for energy consumption and efficiency considerations, it is more appropriate to control the reaction time within 10 hours.
[0208] Compared with Example 1, in Example 23, the reaction pressure is higher, the pressure of the monomer entering the reaction liquid is higher, and more monomers enter the reaction liquid, which can lead to the occurrence of a large-scale polymerization reaction, resulting in an increase in the amount of polyvinylidene fluoride generated. As the monomers decrease, the polyvinylidene fluoride lacks the supply of monomers and the molecular weight generated is relatively small, which has a certain impact on the battery performance.
[0209] Compared with Example 1, in Comparative Example 2, the reaction temperature is relatively low, the driving force of copolymerization is relatively small, the polymerization reaction is insufficient, and the prepared molecular weight is relatively small, resulting in a significant decrease in adhesion at the same addition amount and a significant decrease in cycle performance.
[0210] Compared with Example 1, in Comparative Example 3, the polymerization reaction time is shorter, the polymerization reaction cannot be continued, and the prepared molecular weight is smaller, which also causes a decrease in adhesion and cycle performance.
[0211] Compared with Example 1, in Comparative Example 4, the reaction pressure is lower, the pressure of the monomer entering the reaction liquid is lower, the reaction monomer cannot be continuously replenished, which is not conducive to the continuous polymerization. The molecular weight of the obtained product is too low to meet the requirements for adhesion, and the battery cycle performance is also reduced.
[0212] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0213] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent. It should be noted that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A secondary battery, characterized in that: It includes a positive electrode sheet, a separator and a negative electrode sheet, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet; The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a binder, the binder includes polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million, the polyvinylidene fluoride includes a homopolymer formed by polymerization of vinylidene fluoride monomers, and the crystallinity of the polyvinylidene fluoride is 38% to 48%.
2. The secondary battery according to claim 1, characterized in that: The weight average molecular weight of the polyvinylidene fluoride is 1.8 to 3.2 million.
3. The secondary battery according to claim 1 or 2, characterized in that: The polydispersity coefficient of the polyvinylidene fluoride is 1.5 to 2.
5.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The polydispersity coefficient of the polyvinylidene fluoride is 2 to 2.
3.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 600,000 to 3,000,000.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 1 to 2 million.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The Dv50 particle size of the polyvinylidene fluoride is 50 μm to 150 μm.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The Dv50 particle size of the polyvinylidene fluoride is 60 μm to 100 μm.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The crystallinity of the polyvinylidene fluoride is 40% to 45%.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The viscosity of the binder solution prepared by dissolving the polyvinylidene fluoride in N-methylpyrrolidone is 3500mPa·s to 5000mPa·s, and the mass percentage of the binder in the binder solution is 3% to 5%.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: In the positive electrode active material layer, the mass percentage of the binder is 0.6% to 1.2%.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: In the positive electrode active material layer, the mass percentage of the binder is 0.6% to 0.8%.
13. A binder, characterized in that: The invention comprises polyvinylidene fluoride with a weight average molecular weight of 1.5 to 5 million, wherein the polyvinylidene fluoride comprises a homopolymer formed by polymerization of vinylidene fluoride monomers, and the crystallinity of the polyvinylidene fluoride is 38% to 48%.
14. The adhesive according to claim 13, characterized in that The weight average molecular weight of the polyvinylidene fluoride is 1.8 to 3.2 million.
15. The adhesive according to claim 13 or 14, characterized in that: The polydispersity coefficient of the polyvinylidene fluoride is 1.5 to 2.
5.
16. The adhesive according to any one of claims 13 to 15, characterized in that: The polydispersity coefficient of the polyvinylidene fluoride is 2 to 2.
3.
17. The adhesive according to any one of claims 13 to 16, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 600,000 to 3,000,000.
18. The adhesive according to any one of claims 13 to 17, characterized in that: The number average molecular weight of the polyvinylidene fluoride is 1 to 2 million.
19. The adhesive according to any one of claims 13 to 18, characterized in that: The Dv50 particle size of the polyvinylidene fluoride is 50 μm to 150 μm.
20. The adhesive according to any one of claims 13 to 19, characterized in that The Dv50 particle size of the polyvinylidene fluoride is 60 μm to 100 μm.
21. The adhesive according to any one of claims 13 to 20, characterized in that The crystallinity of the polyvinylidene fluoride is 40% to 45%.
22. The adhesive according to any one of claims 13 to 21, characterized in that The viscosity of the binder solution prepared by dissolving the polyvinylidene fluoride in N-methylpyrrolidone is 3500mPa·s to 5000mPa·s, and the mass percentage of the binder in the binder solution is 3% to 5%.
23. A method for preparing the adhesive according to any one of claims 13 to 22, characterized in that: The following steps are involved: The vinylidene fluoride monomer is polymerized in a non-reactive gas atmosphere, a reaction pressure of 6MPa to 8MPa, and a reaction temperature of 45°C to 60°C for 6h to 10h; A chain transfer agent is added, and when the pressure in the reaction system drops to 2MPa-2.5MPa, the reaction is stopped, the solid and liquid are separated, and the solid phase is retained.
24. The preparation method according to claim 23, characterized in that: The chain transfer agent includes one or more of cyclohexane, isopropanol, methanol and acetone.
25. The preparation method according to any one of claims 23 to 24, characterized in that: The amount of the chain transfer agent used is 1.5% to 3% of the mass of the vinylidene fluoride monomer.
26. The preparation method according to any one of claims 23 to 25, characterized in that: The polymerization reaction comprises the following steps: Adding a solvent and a dispersant into a container, evacuating the container and then filling it with a non-reactive gas; Adding an initiator and a pH adjuster into the container, adjusting the pH value to 6.5-7, and then adding the vinylidene fluoride monomer to make the pressure in the container reach 6MPa-8MPa; After stirring for 30 to 60 minutes, the temperature is raised to 45 to 60° C. to carry out the polymerization reaction.
27. The preparation method according to claim 26, characterized in that: The amount of the solvent used is 2 to 8 times the mass of the vinylidene fluoride monomer.
28. The preparation method according to any one of claims 26 to 27, characterized in that: The dispersant includes one or more of cellulose ether and polyvinyl alcohol.
29. The preparation method according to claim 28, characterized in that: The cellulose ether includes one or more of methyl cellulose ether and carboxyethyl cellulose ether.
30. The preparation method according to any one of claims 26 to 29, characterized in that: The amount of the dispersant used is 0.1% to 0.3% of the mass of the vinylidene fluoride monomer.
31. The preparation method according to any one of claims 26 to 30, characterized in that: The initiator is an organic peroxide.
32. The preparation method according to claim 31, characterized in that: The organic peroxide includes one or more of tert-amyl peroxypivalate, tert-amyl peroxypivalate, 2-ethyl peroxydicarbonate, diisopropyl peroxydicarbonate and tert-butyl peroxypivalate.
33. The preparation method according to any one of claims 26 to 32, characterized in that: The amount of the initiator used is 0.15% to 1% of the mass of the vinylidene fluoride monomer.
34. The preparation method according to any one of claims 26 to 33, characterized in that: The pH adjuster includes one or more of potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate and ammonia water.
35. The preparation method according to any one of claims 26 to 34, characterized in that: The amount of the pH regulator is 0.05% to 0.2% of the mass of the vinylidene fluoride monomer.
36. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 12.
37. A battery pack, characterized in that: Comprising the battery module as claimed in claim 36.
38. An electrical device, characterized in that: It comprises one or more of the secondary battery according to any one of claims 1 to 12, the battery module according to claim 36, and the battery pack according to claim 37.
Citation Information
Patent Citations
Lithium ion secondary battery as well as composition for porus diaphragm layer of the same
CN101276895A
Separator for non-aqueous secondary battery and non-aqueous secondary battery
CN111052449A